Audiological and otological diagnostic features in secretory otitis media - Lal KK (Journal of All India Institute of Speech and Hearing, 1970)
Secretory Otitis Media occupies an unique place in otology and represents one of the most frequent and challenging problems for the Otologist today because of its cause and subtle manifestations of signs and symptoms both in children and adults